2001
DOI: 10.1103/physrevb.63.064304
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency Raman excitations in phase I of solidH2:Role of crystal fields

Abstract: Low-frequency Raman spectra ͑up to 800 cm Ϫ1 ) measured below 18 K are reported for the entire pressure range of phase I of para-hydrogen doped with low fractions of the ortho-modification. In addition to bands corresponding to the E 2g optical phonon and the Jϭ2←0 rotational transitions, we observed a weak band attributed as S 0 (1). These spectra are employed to deduce information on the interactions that play a decisive role in bringing about the transition to the broken symmetry phase II. A new theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…These results are in accord with conclusions made by Goncharov et al in Ref. 24. The authors have measured low-frequency Raman spectra at low temperature for the pressure range up to the I-II phase transition.…”
supporting
confidence: 82%
“…These results are in accord with conclusions made by Goncharov et al in Ref. 24. The authors have measured low-frequency Raman spectra at low temperature for the pressure range up to the I-II phase transition.…”
supporting
confidence: 82%
“…While understanding the orientational transition in ortho-para mixtures of quantum rotors in two and three dimensions is a problem of long-standing theoretical and experimental interest [13,14,15,16,17,18,19,20,21], less attention has been given at establishing the effects of ortho-para distinction. Exceptions [13,14,15,16] are the investigation of vibrons in ortho-para mixtures by Feldman et al [13] and a recent work by Goncharov et al [14], where ortho-D 2 mixed with small amounts of para-D 2 indicated that the possibility of an orientationally frustrated phase between phases I and II (phase II'). Phase II' persisted for a narrow pressure range (∼ 2GPa) for a thermally equilibrated ortho-para mixture.…”
mentioning
confidence: 99%
“…In addition, our simulations do not account for nuclear exchange effects such as those that occur in ortho and para molecules, which are known to be important in a quantitative description of phase I and its transition to phase II [44][45][46][47] . Notwithstanding these limitations, it is clear that quantum nuclear effects and molecular rotations play a very important role in the transition between phases I and II and the transition is strongly quantum in nature even when nuclear exchange is neglected.…”
Section: Discussionmentioning
confidence: 99%